Manuskrip Arab sebagai Argumen Islam Asia Tenggara - Fathurahman, Oman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
This article is a critical review of Peacock's book on “Arabic Literary Culture in Southeast Asia in the Seventeenth and Eighteenth Centuries”. The book reflects the author's attention to the marginalization of the Arabic texts that are composed in the 17th and 18th century Southeast Asia, or for a Southeast Asian audience, and the Arabic texts that were read and copied in the region. Peacock based his analysis on a corpus of Arabic manuscripts in Southeast Asia from different collections in Banten, Jakarta National Library, and others. Peacock argues that in term of Islamic studies, scholars should not regard Southeast Asian Islam as peripheral, regardless its geographical position remotely from the Middle East. One of Peacock’s important arguments is that the royal court became the major centre for the writing and reading of an indigenous Southeast Asian Arabic literature before nineteenth century.